Phomopsis longanae Chi-Induced Change in ROS Metabolism and Its Relation to Pericarp Browning and Disease Development of Harvested Longan Fruit - Wang, Hui; Chen, Yihui; Lin, Hetong; Sun, Junzheng; Lin, Yifen; Lin, Mengshi (Frontiers in Microbiology, 2018)
Phomopsis longanae Chi is a major pathogenic fungus that infects harvested longan fruit. This study aimed to investigate the effects of P. longanae on reactive oxygen species (ROS) metabolism and its relation to the pericarp browning and disease development of harvested longan fruit during storage at 28°C and 90% relative humidity. Results showed that compared to the control longans, P. longanae-inoculated longans displayed higher indexes of pericarp browning and fruit disease, higher O2-. generation rate, higher accumulation of malondialdehyde (MDA), lower contents of glutathione (GSH) and ascorbic acid (AsA), lower 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging ability and reducing power in pericarp. In addition, P. longanae-infected longans exhibited higher activities of superoxide dismutase (SOD), catalase (CAT), and ascorbate peroxidase (APX) in the first 2 days of storage, and lower activities of SOD, CAT, and APX during storage day 2–5 than those in the control longans. These findings indicated that pericarp browning and disease development of P. longanae-infected longan fruit might be the result of the reducing ROS scavenging ability and the increasing O2-. generation rate, which might lead to the peroxidation of membrane lipid, the loss of compartmentalization in longan pericarp cells, and subsequently cause polyphenol oxidase (PPO) and peroxidase (POD) to contact with phenolic substrates which result in enzymatic browning of longan pericarp, as well as cause the decrease of disease resistance to P. longanae and stimulate disease development of harvested longan fruit.